2017
DOI: 10.4081/mr.2017.7330
|View full text |Cite
|
Sign up to set email alerts
|

Impact of unhygienic conditions during slaughtering and processing on spread of antibiotic resistant Escherichia coli from poultry

Abstract: Antibiotic resistance in Escherichia coli is a global health concern. We studied all possible routes of cross contamination of broiler meat with resistant E. coli from broiler feces at poultry shops. Various sample categories namely poultry feces, meat (n=225 for each), slaughterer hands, consumer hands, slaughterer knife, canister, tap water, carcass, feed and drinking water (n=50 for each) were collected from local poultry processing market. Samples were screened for prevalence of E. coli, resistance of isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…As expected, the number of AMR Although the high level of AMR and MDR positivity of the animal feeds generates concern about the spread of genetic determinants conferring drug resistance into the farm and their potential impact on public health, it is not an uncommon finding [8]. The contamination of animal feeds with AMR strains of many bacterial pathogens has been repeatedly reported in the past [3,4,21,22]. This problem seems to be associated with the production line of animal feeds, which is prone to contamination that is very difficult to be prevented in practice.…”
Section: Discussionmentioning
confidence: 95%
“…As expected, the number of AMR Although the high level of AMR and MDR positivity of the animal feeds generates concern about the spread of genetic determinants conferring drug resistance into the farm and their potential impact on public health, it is not an uncommon finding [8]. The contamination of animal feeds with AMR strains of many bacterial pathogens has been repeatedly reported in the past [3,4,21,22]. This problem seems to be associated with the production line of animal feeds, which is prone to contamination that is very difficult to be prevented in practice.…”
Section: Discussionmentioning
confidence: 95%
“…A systematic review by Simoneit et al (2015), showed oral administration of antimicrobials increases antimicrobial resistance E. coli from chicken. Resistant bacteria from intestinal contents can contaminate chicken carcasses at various stages of the chicken slaughtering process (Amir et al ,2017). The percentages of antibiotic-resistant strains among genera of Enterobacteriaceae from broiler chicken meat isolates were significantly higher (P < 0.05) than that from backyard chicken meat isolates (Table 3).…”
Section: Resistance Patternsmentioning
confidence: 98%
“…Enterobacteriaceae can cause severe infections, and some important members of this family are becoming increasingly resistant to currently available antimicrobials (Delgado-Valverde et al, 2013). During evisceration after slaughtering, resistant bacteria from the animal intestine can contaminate chicken carcasses; therefore, chicken meat is often contaminated with resistant bacteria (Rasschaert et al, 2007;Amir et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Although studies are limited, especially on bacteria from wildlife, several studies have been conducted on the antibiotic resistance patterns within a meat processing facility and conclude that cross-contamination of antibiotic resistant bacteria onto the meat does occur and originates from various sources such as the animal feces, staff hands or facility equipment and machinery ( Amir et al, 2017 ; Aslam et al, 2003 ; Schlegelová et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%